The Relative Age Effects on Senior Weightlifting Athletes in Turkey - Tüfekçi, Osman; Erdağı, Kenan; Işık, Bülent (Progress in Nutrition, 2022)
Relative age effect has been used to refer to the age differences between individuals who have been grouped together in a sports competition. The aim of this study is to analyze the birth date distribution of the senior athletes in olympic style weightlifting, who participated in Turkish Weightlifting Championships between the years 2018 and 2020. This study also aims to find out the quarter of the year in which elite athletes with ranking in the first three in weightlifting championships were born. The data collection was obtained from the website of the Turkish Weightlifting Federation with a sample made of 478 senior athletes in the last five Turkish Weightlifting Championships (2018, 2019 and 2020). The players’ birthdates were classified into four seasons of 3 months starting from January to March inclusive (Q1) and ending with October to December inclusive (Q4). The weightlifters were divided into subset weight categories; lightweight, middleweight, heavyweight. The quarter of the year in which elite senior athletes ranking in the first three in championships were born was also obtained. The data was analyzed using SPSS version 25 series of Chi-Square tests. Statistical significance level was set at p< 0,05. In male group of the study, the relative age effects were determined in lightweight (χ²(3)= 28.08, p <.001) and middleweight category (χ²(3)= 23.60, p <.001). Significant relative age effects for female athletes were observed in middleweight category (χ²(3)= 13,15, p <.01). Both for male and female groups, the athletes ranking in the first three in the competitions were observed to be born in the first quarter of the year (χ²(3)= 10.57, p <.01); (χ²(3)= 11.68, p <.01) respectively). In male and female senior groups, significant relative age effects are present on athletes in olympic style weightlifting regardless of their body weight category.